THE ISSUE OF POETIC MASTERY IN MUHAMMAD RAHIMKHAN FERUZ’S CREATIVE WORK - Alishova Aynura (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA’LIMNING INNOVATSION YO’NALISHLARI, 2026)
This article examines the unique features of poetic excellence in the works of Muhammad Rahimkhan Feruz, focusing on the fundamental qualities of his poetic artistry, his mastery in employing literary and visual devices, and the challenges of interpreting national poetic traditions within a modern context.